Mental health and well-being of police in a health pandemic: Critical issues for police leaders in a post-COVID-19 environment - Jacqueline M. Drew; Sherri Martin (Journal of Community Safety and Well-Being, 2020)
Law enforcement is an occupational group that is more “at risk” of physical and psychological harm, as its members are called on to be first responders to critical incidents, terrorist attacks, natural disasters, and traumatic events. This paper explores how the COVID-19 pandemic has provided new and somewhat unique conditions under which police must serve their communities. The scope of involvement and implications for the physical and psychological health and safety of law enforcement officers across the world is unprecedented—impacting every frontline officer on every shift. Build-ing on an evidence-based review of research from previous events such as the World Trade Center attacks on 9/11 and Hurricane Katrina, this paper develops key insights about the likely impact of COVID-19 on the mental health of police. A call to action for police chiefs and their leadership teams, including actionable recommendations to guide strategic and operational plans, is presented. Consideration must not only be given to the issues faced by police during the active COVID-19 period. Police chiefs and police leadership teams must plan and prepare now to meet the mental health legacy that COVID-19 will leave in its wake, months and possibly years later.